Discriminate scoring skills and non-scoring skills according to results in the Brazilian men`s volleyball SuperLeague - Ferreira Oliveira, A. O. G.; Teixeira Vaz, L. M.; Pastore, J. C.; João, P. V. (Montenegrin Journal of Sports Science and Medicine, 2018)
This study analysed the Brazilian SuperLeague Men`s Volleyball 2011/2012 season and 2012/2013 season, in an attempt to identify the game-related factors allowing the determination of winning and losing teams. All games (n=294) of the Brazilian SuperLeague Men`s Volleyball 2011/2012 season and 2012/2013 season were analysed. In the 2011/2012 season, the Total Set Actions (TSETA) and Total Points Made (TPM) were factors that determined the game result as a defeat. The factor that determined the victory was the Total Attack Actions (TAA). In the 2012/2013 season, the factors Total Serve Actions (TSA) and Total Set Actions (TSETA) generated victory, and the factors that led to defeat were the TPM and TAA. The scoring skill (TPM) determined the final game result but surprisingly is associated with the defeat and the TSA with victory. The scoring skill (TAA) determining the result of the game was probably associated with victory in the 2011/2012 season and defeat in the 2012/2013 season. The non-scoring skill TSETA determined the result of the game, and this may be associated with defeat in the 2011/2012 season and the victory in the 2012/2013 season.